A biographical study of social deixis of address terms toward Diana in Spencer (2021) - Asti Rahmaaulia; Nasya Aulia Putri; Cecep Agus (Universitas Pakuan, 2026)
This study explores the use of social deixis through address terms directed toward Diana in the biographical film Spencer (2021). As a pragmatic phenomenon, social deixis reflects hierarchical relations, politeness strategies, and identity negotiation within discourse. Employing a qualitative-biographical approach, the research analyzes utterances from the film’s script, classified according to Levinson’s (1983) framework of absolute and relational social deixis. The findings reveal that address terms function systematically across four categories: differentiating social levels, maintaining politeness, signaling social identity, and enhancing sentence effectiveness. These linguistic markers demonstrate how institutional authority is reinforced through honorifics such as Your Royal Highness and Ma’am, while intimate terms like Mummy highlight Diana’s identity. From a biographical lens, the study shows that language becomes a site of tension between Diana’s institutional role and personal self. The research contributes to pragmatic studies by illustrating how address terms reproduce power relations and fragment identity within monarchical discourse.